2020
DOI: 10.1111/jfbc.13484
|View full text |Cite
|
Sign up to set email alerts
|

Malus hupehensis leaves extract attenuates obesity, inflammation, and dyslipidemia by modulating lipid metabolism and oxidative stress in high‐fat diet‐induced obese mice

Abstract: Malus hupehensis leaves (MHL) are used to make traditional Chinese tea. In this study, MHL extract was shown to improve metabolic disorders and inflammatory response in high-fat diet-induced obese mice. MHL extract could reduce body weight, and significantly alleviate liver damage and fat accumulation. MHL extract caused a decrease in the levels of ALT, AST, AKP, TC, TG, LDL-C, and an increase in the level of HDL-C. It also caused a decrease in inflammatory cytokines, including TNF-α, IFN-γ, IL-1β, IL-6, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…FAS also activates CPT1, an essential enzyme during fatty acid β‐oxidation and is associated with diabetes and obesity. The CPT1 gene is a downstream PPAR‐γ target, and PPAR‐γ regulates its expression level to control lipid metabolism and lipid deposition (Lundsgaard et al ., 2018; Wu et al ., 2020). In our study, PCP treatment significantly suppressed the HFD‐induced mice model, which increases after the mRNA expression of PPARγ, C/EBPα and SREBP‐1c, indicating that the PCP effects in reducing body weight were regulated through lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FAS also activates CPT1, an essential enzyme during fatty acid β‐oxidation and is associated with diabetes and obesity. The CPT1 gene is a downstream PPAR‐γ target, and PPAR‐γ regulates its expression level to control lipid metabolism and lipid deposition (Lundsgaard et al ., 2018; Wu et al ., 2020). In our study, PCP treatment significantly suppressed the HFD‐induced mice model, which increases after the mRNA expression of PPARγ, C/EBPα and SREBP‐1c, indicating that the PCP effects in reducing body weight were regulated through lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was whirled for 1 min and then centrifuged at 15,000 g , at 4°C for 10 min. The collected supernatant was used for liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) analysis (Wu, Guo, et al., 2020; Wu, Sun, et al., 2020; Xie et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It is a high‐risk factor for a number of severe diseases including diabetes, arteriosclerosis, high blood pressure, circulatory diseases, and respiratory diseases (Kim, Koo, et al., 2020; Kim, Kim, et al., 2020; Terao et al., 2020). Among the various causes of obesity, the imbalance between energy storage and consumption is crucial (Gan et al., 2020; Wu, Guo, et al., 2020; Wu, Sun, et al., 2020). Many epidemiologic studies have reported that excessive nutrition and lack of exercise result in the accumulation of fat and obesity (Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 μL test solution was injected, the chromatographic peak area was obtained at detection wavelength of 285 nm. 22 The compounds in GPFE were analyzed according the chromatographic peak area of standard substance.…”
Section: Determination Of Gpfe Compositionmentioning
confidence: 99%